Integrating Large-Scale Genomic Information into Clinical Practice : Workshop Summary. - Olson, Steve, 1956- (National Academy Press, 2012)
The initial sequencing of the human genome, carried out by an international group of experts, took 13 years and $2.7 billion to complete. In the decade since that achievement, sequencing technology has evolved at such a rapid pace that today a consumer can have his or her entire genome sequenced by a single company in a matter of days for less than $10,000, though the addition of interpretation may extend this time frame. Given the rapid technological advances, the potential effect on the lives of patients, and the increasing use of genomic information in clinical care, it is important to address how genomics data can be integrated into the clinical setting. Genetic tests are already used to assess the risk of breast and ovarian cancers, to diagnose recessive diseases such as cystic fibrosis, to determine drug dosages based on individual patient metabolism, and to identify therapeutic options for treating lung and breast tumors, melanoma, and leukemia. With these issues in mind and considering the potential impact that genomics information can have on the prevention, diagnosis, and treatment of disease, the Roundtable on Translating Genomic-Based Research for Health hosted a workshop on July 19, 2011, to highlight and identify the challenges and opportunities in integrating large-scale genomic information into clinical practice. Integrating large-scale genomic information into clinical practice summarizes the speaker presentations and the discussions that followed them. This report focuses on several key topics, including the analysis, interpretation, and delivery of genomic information plus workforce, ethical, and legal issues.